The Effect of Compensation and Competency on Employee Performance At The Production Department Of PT. FCC Indonesia - Agung Prayogo; Asep Jamaludin; Nandang Nandang (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study aims to describe how the influence of compensation (X1) and Competency (X2) as independent variables on employee performance (Y) as the dependent variable in the Production Department of PT FCC Indonesia. Verifiatively, the aim is to test the hypothesis by calculating statistics about the effect of compensation and Competency on employee performance. This study used descriptive quantitative methods, and data were collected by distributing questionnaires to 155 respondents from employees of PT FCC Indonesia througha simple random sample. Data analysis was carried out using path analysis and the help of the SPSS application. The results show that the compensation, Competency, and employee performance variables have good scores descriptively. Verifiatively, there is a partial effect of compensation on employee performance and a partial effect of Competency on employee performance.